Perbedaan Kenaikan Berat Badan dan Kadar Hemoglobin pada Ibu Hamil Primigravida dengan Multigravida - Dinda Aziza Bryllianna; Hendarto, Hendy; Henderi, Hendera (SENTRI: Jurnal Riset Ilmiah, 2026)
Maternal Mortality Rate (MMR) remains a major challenge in public health, making the monitoring of pregnant women’s onditions, including hemoglobin (Hb) levels and weight gain highly important. This study aims to analyze the differences in hemoglobin levels and weight gain between primigravida and multigravida pregnant women at Made Public Health Center. This research employed a comparative quantitative approach with a cross-sectional design and utilized secondary data from medical records. The sample consisted of 78 respondents selected through stratified random sampling based on gravida status. The variables examined included gravida status as the independent variable and hemoglobin levels as well as weight gain as the dependent variables. Data were analyzed using the Chi-Square test with a significance level of p < 0.05. The results showed a statistically significant difference between gravida status and hemoglobin levels (p = 0.003), with multigravida mothers having a 4.5-times higher risk of experiencing anemia compared to primigravida mothers. Additionally, there was a statistically significant difference between gravida status and weight gain during pregnancy (p = 0.000), where multigravida mothers had a 7.3-times higher risk of experiencing abnormal weight gain. These findings highlight that gravida status is closely related to the nutritional status of pregnant women and can serve as a basis for evaluating antenatal care services, particularly for the multigravida group who are at higher risk.